In memory of warrior Alexander Klimov (2000–2025) - Sergey V. Novikov (Вестник Екатеринбургской духовной семинарии)
Alexander Ruslanovich Klimov (28.08.2000–23.03.2025) was a former undergraduate student of the Ekaterinburg Theological Seminary who died while performing military duty in the zone of the special military operation. The article highlights his life path: childhood in a religious family, military service, studies at the seminary where he was remembered as a responsive and hardworking person (nicknamed «Sasha the Blacksmith»). Special attention is paid to his last battle near Chasov Yar, where he covered wounded comrades from drone attacks. The material is based on memoirs of classmates, seminary teachers and combat comrades.